A study of Information Processing effectiveness in inter-organisational collaboration in Software Development. (19th September 2011) - Mohtashami, Mojgan; Sylla, Cheickna; Im, Il; Deek, Fadi P.
Effective coordination and collaboration are key success factors in management of inter-organisational alliances, although questions related to best practices remain unanswered. Few studies have identified communication, effective information sharing and knowledge extraction as integral components of inter-organisational collaboration. This research focuses on the role and effectiveness of Information Processing (IP), as well as information utilisation across organisational boundaries. Proposed is a set of factors in three categories related to organisational background, contingency process and information technology processing capacity to investigate if higher levels of these factors will result in higher levels of IP, and if this will result in higher levels of Software Development (SD) effectiveness.